The Influence of the MRSP on the Freezing and Evaporation Processes of the Magnesium Sulfate Subtype Salt Lake Brine. (30th August 2016) - Li, Qinghai; Zhu, Kongjin; Liu, Yuntao; Liu, Xingqiang; Li, Feng; Liu, Guoju; Yang, Yong; Li, Yonghua; Liu, Shenglin; Song, Wenyi
Abstract : We have developed a new concept, which is the mass fraction ratio of sulfate and potassium ions (MRSP), for the magnesium sulfate subtype salt lake, which is calculated using the metastable phase diagram. We also studied the trend of the MRSP values with the temperature and the influence of the MRSP values on the evaporation process. The experimental results indicated that the MRSP value showed significantly negative trend with decrease of refrigerated temperature. Moreover, when the MRSP value of the objective brine is reduced to less than or equal to the Specific Value by freezing operation, the great changes of crystal morphology and stage of K + andS O 4 2 - will take place, which makes the sequence of salts precipitation of the freezing-evaporation different from the direct-evaporation.